rSodC is a potential antigen to diagnose Corynebacterium pseudotuberculosis by enzyme-linked immunoassay - Farias, Antonio Pedro Fróes de; Rocha Filho, José Tadeu Raynal; Marchioro, Silvana Beutinger; Moreira, Luan Santana; Marques, Andressa Souza; Sá, Maria da Conceição Aquino de; Oliveira, Antonio Anderson dos Santos; Alcântara, Maria Emília; Mariutti, Ricardo Barros [UNESP]; Arni, Raghuvir Krishnaswamy [UNESP]; Trindade, Soraya Castro; Meyer, Roberto (Springer Nature, 2020)
Caseous lymphadenitis (CL) is a chronic infectious disease that affects sheep and goats. Many serological tests have been developed to detect the disease; one of the most widely used is the enzyme-linked immunosorbent assay (ELISA), due to its advantages, which include acceptable cost-effectiveness, applicability, sensitivity and specificity. ELISA formulations using recombinant proteins can exhibit significant sensitivity and specificity when using a single purified antigen. DTxR, Trx, TrxR, LexA, SodC, SpaC, NanH, and PknG recombinant proteins can be considered target proteins for ELISA development due to its extracellular or on the cell surface location, which allows a better recognition by the immune system. Therefore, the objectives of this study were to evaluate the antigenic reactivity of Corynebacterium pseudotuberculosis recombinant proteins in goat and sheep serum. Of eight proteins evaluated, rSodC was selected for validation assays with small ruminant serum samples from the semiarid region of the state of Bahia, Brazil. Validation assays with goat serum samples showed that ELISA-rSodC presented sensitivity and specificity of 96% and 94%, respectively. Validation assays with sheep serum showed that ELISA-rSodC exhibited sensitivity and specificity of 95% and 98%, respectively. Analysis of 756 field serum samples showed that rSodC identified 95 positive samples (23%) in goats and 75 positive samples (21%) in sheep. The ELISA with recombinant SodC protein developed in this study discriminated positive and negative serum samples with high levels of sensitivity and specificity. This formulation is promising for epidemiological surveys and CL control programs. Trial registration AEC No 4958051018. 12/18/2018, retrospectively registered
Keywords: Caseous lymphadenitis; Corynebacterium pseudotuberculosis; ELISA; SodC recombinant protein